2000
DOI: 10.1023/a:1005424603085
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Clinical-endoscopic parameters of UC presentation were studied in 1705 out-patients, observed consecutively in 17 Italian gastroenterology centers (males 60.2%; average age at diagnosis 38.5 +/- 16.4 years), and were subdivided arbitrarily into quartile age groups at diagnosis (0-25, 26-35, 36-50, >50). A significantly greater prevalence in males, increasing with age, was shown at diagnosis (P = 0.0002), which seems to correlate with the condition of being an ex-smoker, most frequently found in males. The grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 21 publications
3
23
1
Order By: Relevance
“…Our findings are consistent with results previously published which demonstrated that later age of diagnosis was associated with less extensive disease [8, 12, 13, 16]. In a retrospective review of 93 patients with ulcerative colitis, proctitis was found to be more common among patients with ulcerative colitis diagnosed after age 50 ( p = 0.077) [13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with results previously published which demonstrated that later age of diagnosis was associated with less extensive disease [8, 12, 13, 16]. In a retrospective review of 93 patients with ulcerative colitis, proctitis was found to be more common among patients with ulcerative colitis diagnosed after age 50 ( p = 0.077) [13].…”
Section: Discussionsupporting
confidence: 92%
“…An evaluation of a population cohort of newly diagnosed UC patients revealed that patients diagnosed at 65 years or older were more likely to be hospitalized for the first attack of disease and more likely to receive steroids [7]. Conversely, an Italian study found that steroid use was used more frequently in younger patients [8]. However, this study as well as a case–control study of patients from the Mayo Clinic failed to demonstrate a higher rate of colectomy in the elderly [7, 9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CD patients, terminal ileal location (L1), stricturing (B2) or penetrating (B3) behavior and age under 40 years at diagnosis were independent risk factors for subsequent bowel surgery [18]. These findings were in line with both previous and later European population-based studies [21,22,23,27,28]. Extensive colitis at presentation (defined as macroscopic lesions with an upper limit proximal to the splenic flexure) has consistently been shown to be the most important and independent predictor of the need for a colectomy within the first 10 years after diagnosis [21,22,29,30].…”
Section: Can We Predict Serious Disease Outcomes?supporting
confidence: 71%
“…However, it is unclear whether these differences in age distribution influence clinical features and disease behavior; therefore, it is important to understand the differences between early and late onset UC. Previous studies examining the natural history of UC in elderly patients have yielded conflicting results: some studies suggested that late-onset UC is more aggressive and associated with higher rates of complications, IBD-related hospitalization, and mortality [1,4,5,6,7], whereas several other studies indicated that older age at diagnosis initially increased the recurrence risk but was subsequently protective, with older patients less likely to require immunosuppressants or admission for disease flares [8,9]. In addition, these investigations were exclusively undertaken in Western countries and there is little information on the disease course of UC in relation to the age at onset in Asian populations.…”
Section: Introductionmentioning
confidence: 99%